Elevated Brain Glutamate Levels in Bipolar Disorder and Pyruvate Carboxylase-Mediated Anaplerosis - Shen, Jun; Tomar, Jyoti Singh (Frontiers in Psychiatry, 2021)
In vivo 1H magnetic resonance spectroscopy studies have found elevated brain glutamate or glutamate + glutamine levels in bipolar disorder with surprisingly high reproducibility. Because brain relies on pyruvate carboxylase-mediated anaplerosis in astrocytes for de novo glutamate synthesis we propose that the elevated glutamate levels in bipolar disorder can be explained by increased pyruvate carboxylase-mediated anaplerosis in brain. Multiple independent lines of evidence supporting increased pyruvate carboxylase-mediated anaplerosis as a common mechanism underlying glutamatergic hyperactivity in bipolar disorder and the positive association between bipolar disorder and obesity are also described.